Epistemologi Ilmu Dalam Perspektif Filsafat Kontemporer: Sebuah Tinjauan Sistematis - Marchelia, Keni (Journal of Innovation in Teaching and Instructional Media, 2025)
Epistemology, as a branch of philosophy that studies the theory of knowledge, continues to develop in various perspectives, especially in contemporary philosophy. This article examines the view of epistemology of science in the context of contemporary philosophy, by highlighting the paradigm shift from classical theory of knowledge towards a more dynamic and open understanding. The main focus of this research is to identify and analyze key concepts in contemporary epistemology, such as constructivism, pragmatism, post-structuralism, and social knowledge theory. By examining the contributions of key figures such as Michel Foucault, Ludwig Wittgenstein, and Thomas Kuhn, this article reveals how the development of science is influenced by social, cultural, and historical contexts, and how knowledge is constructed, questioned, and acquired. Through this systematic review, this article aims to provide a deeper understanding of the epistemological dynamics that occur in the contemporary era, as well as the implications for the development of science and the scientific method today. This research uses the SRL (systematic literature review) method. This research method uses a Systematic Literature Review (SLR) study. The references for this writing come from journals from 2020 to 2023. The 15 journals reviewed are national journals and come from Google Scholar.